Pengaruh Budaya Dalam Keberhasilan Konseling - Indah Permata Sari; Wasti Hotmaria Sitanggang; Mukti Lestari Setya Ningsih; Annisa Putri Rinjani; Shelly Marcelina Nababan (Syntax Corporation, 2022)
Pengaruh Budaya Dalam Keberhasilan Konseling